The establishment of fundamental Shariah compliant hospital management in Malaysia - Hamzah, Muhammad Hazrul; Jamaludin, Mohammad Aizat; Md. Sawari, Mohd Fuad (HH Publisher, 2019)
The development of the Halal industry has taken place in many fields including food preparation, farming, logistic, tourism, sports and health. The Shariah Compliant Hospital Management (SCHM) is an examples of a new concept in the healthcare segment derived from the application of Shariah’s Principle into the administration and the delivery services in the hospital. However, the deficiency of research discusses the fundamental requirement of establishing a Shariah Compliant Hospital Management (SCHM) in Malaysia is among the issues confronting. Besides, until this point, the organization is self-claimed because of absence of explicit rules given by the authorities. Thus, this paper attempts to identify the fundamental establishment of Shariah Compliant Hospital Management (SCHM) in Malaysia. Data was gathered through library research and qualitative analysis was carried out employing secondary data obtained. The important elements in establishing Shariah Compliant Hospital Management (SCHM) are to establish Shariah Advisory Council (SAC), appoint Shariah Compliant Officer (SCO) and develop Shariah Critical Point (SCP). These elements acknowledge the healthcare which complies to Shariah in the management level.